Parental involvement during COVID-19: experiences from the special school. Issue 6 (2nd November 2022) - O'Connor Bones, Una; Bates, Jessica; Finlay, Jayne; Campbell, Allison
ABSTRACT: The closure of schools worldwide in response to the COVID-19 pandemic required parents to undertake key pedagogical roles to support their children's education and movement to a remote, often virtual world of online teaching presented many challenges for families. For the parents of children attending special schools, the loss of educational, as well as therapeutic provision, added a further layer of complexity unique to this group. This paper presents findings from a Northern Ireland-wide survey undertaken during the first lockdown period. Using Hornby and Blackwell's model of parental involvement (PI), the paper describes parents' experiences relative to their child's needs, family circumstances and societal expectations, and the intersection of these with teacher relationships and the wider school community. The findings reveal those factors that facilitated and inhibited PI and makes suggestions for improvements at school and policy levels in the short and longer term. The results have relevance and reach beyond the Northern Ireland context and should contribute to international dialogue on the synergy between PI and the special school setting.